Training actors in the Ateneo Theater Arts Program negotiating Western practices within cultural parameters - Abad, Ricardo G.; Maramara, Melissa-Vera M. (2016)
Anglo-American or Western acting practices, largely influenced by the words of Russian theater theorist Konstantin Stanislavsky, lie at the core of acting courses in the Philippines and many countries of the world. In Western societies, these practices are thought in a cultural context where individualism, personal achievement, egalitarianism, and democratic principles are valued. These cultural orientations facilitate the expressions of an actor's inner life. In contrast, the cultural orientations in the Philippines context are a deference to authority, a sense of shame, and an inclination to emotionalism. How, then, does the Ateneo Theater Arts Program, based in a Philippine university, impart Western practices? This paper proposes an answer based on the writer's personal experiences as theater through cultural negotiation enacted in acting exercises, an accommodation between Western acting methods and local cultural imperatives can be reached, a situation that allows Filipino actors to eventually discover their own unique ways of showing inner lives onstage.
Keywords: Acting; Filipino cultural traits